Two theorems on (ϵ)-Sasakian manifolds - Xu Xufeng; Chao Xiaoli (International Journal of Mathematics and Mathematical Sciences)
In this paper, We prove that every (ϵ)-sasakian manifold is a hypersurface of an indefinite kaehlerian manifold, and give a necessary and sufficient condition for a Riemannian manifold to be an (ϵ)-sasakian manifold.